(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2013)
The processes of development are expressed in complex realities where the components of the share capital can stimulate it, specially if they are considered establishing his links with the human development, concept that uses as support alternative models, those who have been restored in the market economies. The present work seeks to establish the joints between the share capital, and his different ways of understanding it, and the possibilities of reaching a few conditions of development that answer integrally to the creation of opportunities, considering new options to be the social economy, to conclude with an offer of lines of investigation that they might extend our knowledge in this matter.